The Cerro Olivo Complex: a pre-collisional Neoproterozoic magmatic arc in Eastern Uruguay - Masquelin, H; Fernandes, L.; lenz, C; Porcher, C.; McNaughton, Neal (Bellwether Publishing, 2012)
The Cerro Olivo Complex is one of the few occurrences of the basement rocks in the Dom Feliciano Belt. It contains migmatitic paragneisses and orthogneisses that host granites of ca. 600–540 Ma Aiguá Batholith. The main orthogneisses are rich in orthopyroxene + Ca-plagioclase (Cerro Bori unit), but K-feldspar augen gneisses are also common (Centinela-Punta del Este unit). The paragneisses (Chafalote unit) are semi-pelitic migmatites that contain restites of metapelites, quartzites, amphibolites, and calc-silicate rocks. A clockwise pressure–temperature–time (P–T-t) path and two deformational events affected the Cerro Olivo Complex rocks. Granulitic high-pressure (HP)–high-temperature (HT) peak conditions were followed by low pressure (LP)–HT decompression. The first deformation (K1) developed an E–W gneissic foliation and westward-stretching lineations, whereas the second (K2) produced NS to NE–SW low-temperature mylonitic foliation and southward-stretching lineations. New SHRIMP U–Pb data from zircon cores in magmatic textural domains yield an intrusive age of 782 ± 7 million years for the Cerro Bori unit. The zircon rims have an age of 657 ± 7 million years, reflecting a younger partial melting event. Inherited ages in zircon xenocrysts span from 2655 to 768 million years, but are mostly ca. 1.0–1.2 thousand million years old. Bulk-rock geochemistry indicates a magmatic arc setting for the source rocks. The Cerro Bori unit represents calk-alkaline tonalitic and granodioritic rocks mixed with minor gabbros; in contrast, the Centinela unit consists of post-orogenic granites. A continental magmatic arc developed between ca. 800 and 770 Ma attending convergence of the Kalahari and Rio de la Plata palaeocontinents, but prior to their collision.